Effects of 469 E/K polymorphism of ICAM1 gene in ischemic stroke and its association with stroke severity and outcome - Pethusamy, Karthikeyan; Seethy, Ashikh A; Kulandhasamy, Maheshwari; Garg, Pinki; Chowdhury, Debashish; Agarwal, Sarita; Kumar, Arun; Dhar, Ruby; Karmakar, Subhradip (Asian Journal of Medical Sciences, 2021)
Background: Stroke is the second leading cause of death globally and it is a major cause of long-term, physical, psychological, and social disability among the elderly. Increasing evidence shows that ischemic injury and inflammation account for its pathogenic progression. So, we studied the association of Intercellular Adhesion Molecule 1 (ICAM1) polymorphism with ischemic stroke, stroke severity, and outcome. Aims and Objectives: To compare ICAM1 469 E/K polymorphism in ischemic stroke patients with healthy controls, and to study its association with stroke severity and outcome. Materials and Methods: Fifty patients of ischemic stroke and hundred healthy individuals were included. The stroke severity was assessed clinically and radiologically. Outcome was measured at three and six months of stroke onset. Genomic DNA was used for Allele-Specific PCR to detect ICAM1 469 E/K polymorphism. The subjects were categorized into EE, EK, and KK genotypes. Results: The odds of EK genotype to develop stroke was 0.41 (95 % CI; 0.17 - 0.92) (p = 0.07) and of KK genotype was 0.41 (95 % CI; 0.11 - 0.87) (p = 0.04) compared to EE genotype. Subjects with ICAM1K allele had significantly reduced risk of stroke compared with those with E allele. (RR: 0.55; 95% CI: 0.35-0.87) (p=0.03). Conclusion: Subjects with ICAM1K allele had significantly reduced the risk of developing stroke. 469 E/K polymorphism of the ICAM1 gene does not significantly affect stroke severity, mortality, and outcome.